MANAGEMENT BY MODES WORKS OF MAIN GAS PIPELINES WITH THE USE OF REGIONS POSSIBLE MODES AND MAXIMUM ENERGY EXPENSES - Грудз, Володимир Ярославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The methods of construction of regions of the possible modes and maximum regions of energy expenses are resulted for the compressor stations of main gas pipelines at different charts of work of gas pumping aggregates over. Principles of optimization of the modes and operative management by work of the system are shown.